The Law and the Prophets: Black Consciousness in South Africa, 1968–1977 - Magaziner, Daniel (New African Histories, 2010)
"No nation can win a battle without faith, " Steve Biko wrote, and as Daniel R. Magaziner demonstrates in The Law and the Prophets, the combination of ideological and theological exploration proved a potent force. The 1970s are a decade virtually lost to South African historiography. This span of years bridged the banning and exile of the country's best-known antiapartheid leaders in the early 1960s and the furious protests that erupted after the Soweto uprisings of June 16, 1976. Scholars thus know that something happened—yet they have only recently begun to explore how and why. The Law and the Prophets is an intellectual history of the resistance movement between 1968 and 1977; it follows the formation, early trials, and ultimate dissolution of the Black Consciousness movement. It differs from previous antiapartheid historiography, however, in that it focuses more on ideas than on people and organizations. Its singular contribution is an exploration of the theological turn that South African politics took during this time. Magaziner argues that only by understanding how ideas about race, faith, and selfhood developed and were transformed in this period might we begin to understand the dramatic changes that took place.